2015
DOI: 10.1016/j.meatsci.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Sire carcass breeding values affect body composition in lambs — 1. Effects on lean weight and its distribution within the carcass as measured by computed tomography

Abstract: and fat depth (mm; PFAT), and post weaning weight (kg; PWWT). Across the 7.8 unit range of sire PEMD, carcass lean weight increased by 7.7%. This lean was distributed to the saddle section (mid-section) where lean became 3.8% heavier, with fore section lean becoming 3.5% lighter. Reducing sire PFAT across its 5.1 unit range increased carcass lean weight by 9.5%, and distributed lean to the saddle section which was 3.7% heavier. Increasing sire PWWT increased lean at some sites in some years, and on average inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 36 publications
5
23
0
3
Order By: Relevance
“…This difference in lean weight was worth $3.58, and aligns well with the sire type effect discussed above where the lean from Merino lambs was worth $4.80 more than lambs from Maternal dams. Although not previously compared on a dollar basis, the mass differences align well with previous studies where, after correcting for carcass weight, lambs from BLM dams had less carcass lean (Anderson, Williams, et al, 2015a;Ponnampalam et al, 2008) and a higher proportion of fat (Anderson, Williams, et al, 2015b) than lambs from Merino dams.…”
Section: The Impact Of Sire Type and Dam Breed On The Value Of The Lasupporting
confidence: 85%
See 4 more Smart Citations
“…This difference in lean weight was worth $3.58, and aligns well with the sire type effect discussed above where the lean from Merino lambs was worth $4.80 more than lambs from Maternal dams. Although not previously compared on a dollar basis, the mass differences align well with previous studies where, after correcting for carcass weight, lambs from BLM dams had less carcass lean (Anderson, Williams, et al, 2015a;Ponnampalam et al, 2008) and a higher proportion of fat (Anderson, Williams, et al, 2015b) than lambs from Merino dams.…”
Section: The Impact Of Sire Type and Dam Breed On The Value Of The Lasupporting
confidence: 85%
“…Non-significant (P > 0.05) terms were removed in a stepwise manner. Although these ASBVs were correlated (PWWT vs PEMD = 0.3; PWWT vs PFAT = 0.3; PEMD vs PFAT = 0.1) previous analysis has demonstrated that their effects are still relatively independent when included simultaneously in a model predicting CT composition (Anderson, Williams, et al, 2015a, 2015b. …”
Section: Establishing Models For Predicting Section Lean Weightsmentioning
confidence: 89%
See 3 more Smart Citations